Relational Marketing Strategies in Building Consumer Trust in Printing Businesses in Padang City - Borry Fonanda; Perengki Susanto; Husnil Khatimah; Fitri Yulianis; Fadil Meiseptian (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
In the digital era, printing businesses face significant challenges in retaining customers due to intense competition and rapidly changing consumer behaviors. Beyond product quality, modern consumers increasingly value transparent, consistent, and meaningful interactions with businesses. This study examines how relational marketing strategies can foster consumer trust in printing businesses. Using a qualitative approach, in-depth interviews were conducted with business owners and customers, and the data were analyzed thematically to identify patterns in relational marketing practices and their impact on trust. Findings reveal that clear and consistent communication, high-quality service, and personalized attention to customer needs strengthen emotional connections and long-term loyalty. The strategic use of digital media facilitates faster and more flexible interactions, while long-term commitments, such as after-sales support, continuous innovation, and loyalty programs, emerge as critical for sustaining trust. These results highlight that consumer trust is not solely built through product quality but also through the ongoing cultivation of relational ties. The study concludes that printing businesses should integrate effective communication, consistent service, personalization, digital engagement, and long-term commitment to enhance customer loyalty and competitive advantage in an increasingly complex market. This research provides practical insights for business owners seeking to strengthen customer relationships and sustain growth in the digital era.